The sacred cow and the new Comer: A comparative study of nation-state and umma - Mohamed, Ayat Abdulaty (AUC Knowledge Fountain, 2015)
International relations discipline witnessed debates among its mainstream theories. Today the debate worthy of attention is the Western-centrism of the discipline. There is an immense critique of the Westphalian state order, the nation-state, and the absence of religion in IR theory. This research aspires to partially account for the voids of the IR theory. It engages with the debate over the Western-centrism and the loopholes of IRT. This thesis introduces a non-Western contribution to international relations, an Islamic perspective of IR. This thesis argues that for IR discipline to be truly pluralistic and to claim universality it should be opened to other non-Western contributions. The thesis introduces the ‘Islamic Civilizational Paradigm’ (ICP), a project developed over a decade from mid 1980s to mid 1990s to lay the foundation of an Islamic theory of IR. The paradigm reflects a different episteme, unlike the mainstream IR theories it introduces a new conceptualization of the relationship between religion and politics; it is a religious-inspired paradigm. Moreover, It escapes the state-centric lens that dictates the analysis in IR by introducing the Umma as a new level of analysis. To explore the advantage of integrating non-Western contributions -in this case the ICP- to IR discipline I focus on the Umma-level compared to state-level and investigate the advantages and limitations of that new level and evaluate its potential feasibility. The thesis concludes that the Umma-level complements the state-level as it has the ability to account for the complexities of the international phenomenon. Even more, through Umma lens we can identify and analyze state and non-state actors, groups, transnational social movements, individuals. The thesis shed light on what the Islamic Civilizational Paradigm presents and how it should be further improved.